Molecular imaging of the prostate: Comparing total sodium concentration quantification in prostate cancer and normal tissue using dedicated 13C and 23Na endorectal coils. Issue 1 (13th May 2019) - Barrett, Tristan; Riemer, Frank; McLean, Mary A.; Kaggie, Joshua D.; Robb, Fraser; Warren, Anne Y.; Graves, Martin J.; Gallagher, Ferdia A.
Abstract : Background: There has been recent interest in nonproton MRI including hyperpolarized carbon‐13 ( 13 C) imaging. Prostate cancer has been shown to have a higher tissue sodium concentration (TSC) than normal tissue. Sodium ( 23 Na) and 13 C nuclei have a frequency difference of only 1.66 MHz at 3T, potentially enabling 23 Na imaging with a 13 C‐tuned coil and maximizing the metabolic information obtained from a single study. Purpose: To compare TSC measurements from a 13 C‐tuned endorectal coil to those quantified with a dedicated 23 Na‐tuned coil. Study Type: Prospective. Population: Eight patients with biopsy‐proven, intermediate/high risk prostate cancer imaged prior to prostatectomy. Sequence: 3T MRI with separate dual‐tuned 1 H/ 23 Na and 1 H/ 13 C endorectal receive coils to quantify TSC. Assessment: Regions‐of‐interest for TSC quantification were defined for normal peripheral zone (PZ), normal transition zone (TZ), and tumor, with reference to histopathology maps. Statistical Tests: Two‐sided Wilcoxon rank sum with additional measures of correlation, coefficient of variation, and Bland–Altman plots to assess for between‐test differences. Results: Mean TSC for normal PZ and TZ were 39.2 and 33.9 mM, respectively, with the 23 Na coil and 40.1 and 36.3 mM, respectively, with the 13 C coil ( P = 0.22 and P = 0.11 for the intercoil comparison, respectively). For tumor tissue, there was no statistical difference between the overall mean tumor TSC measured with the 23 Na coil (41.8 mM) and with the 13 C coil (46.6 mM; P = 0.38). Bland–Altman plots showed good repeatability for tumor TSC measurements between coils, with a reproducibility coefficient of 9 mM; the coefficient of variation between the coils was 12%. The Pearson correlation coefficient for TSC between coils for all measurements was r = 0.71 ( r 2 = 0.51), indicating a strong positive linear relationship. The mean TSC within PZ tumors was significantly higher compared with normal PZ for both the 23 Na coil (45.4 mM; P = 0.02) and the 13 C coil (49.4 mM; P = 0.002). Data Conclusion: We demonstrated the feasibility of using a carbon‐tuned coil to quantify TSC, enabling dual metabolic information from a single coil. This approach could make the acquisition of both 23 Na‐MRI and 13 C‐MRI feasible in a single clinical imaging session. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;51:90–97.